Massive Femoral Osteolysis Secondary to Loosening of a Cemented Roughened Long Stem: A Case Report - Yasuaki Tamaki; Tomohiro Goto; Daisuke Hamada; Toshihiko Nishisho; Kiminori Yukata; Suzue Naoto; Hiroshi Egawa; Koichi Sairyo (Case Reports in Orthopedics)
The surface finish of a femoral stem plays an important role in the longevity of cemented total hip arthroplasty. In efforts to decrease the rate of aseptic loosening, some prostheses have been designed to have a roughened surface that enhances bonding between the prosthesis and cement, but clinical outcomes remain controversial. We present a rare case of massive osteolysis with extreme femoral expansion that developed after cemented revision total hip arthroplasty. The destructive changes in the femur were attributable to abnormal motion of the stem and were aggravated by the roughened precoated surface of the long femoral component. Revision surgery using a total femur prosthesis was performed because there was insufficient remaining bone to fix the new prosthesis. The surgical technique involved wrapping polypropylene meshes around the prosthesis to create an insertion for the soft tissue, which proved useful for preventing muscular weakness and subsequent dislocation of the hip.